Costos directos médicos de pacientes con infecciones de tracto urinario por bacilos gram negativos resistentes a betalactámicos en un hospital de alta complejidad de Medellín, Colombia (2018)
Introduction: Urinary Tract Infections (UTIs) have a high frequency of occurrence in the hospital environment and, due to the emergence of antimicrobial resistance, have caused care processes to become more complex, putting additional pressure on available healthcare resources. Objective: To describe and compare the excess direct medical costs of UTIs due to K. pneumoniae, E. cloacae and P. aeruginosa resistant to beta-lactams. Materials and methods: A cohort study was conducted in a third level institution in Medellín, Colombia, from October 2014 to September 2015. It included patients with UTIs by beta-lactam-susceptible bacteria, 3rd and 4th generation cephalosporins-resistant, and carbapenem-resistant. Costs were analyzed from the perspective of the health system. Clinical-epidemiological information was obtained from medical records and the costs were calculated using standard tariff manuals. Excess costs were estimated with multivariate analyzes. Results: 141 patients were included, 39% of which were sensitive to beta-lactams, 38.3% resistant to cephalosporins and 22.7% resistant to carbapenems. The excess total adjusted costs of patients with UTIs due to resistant bacteria-cephalosporins and carbapenems were US$193 [95% confidence interval (CI) US$-347-734] and US$633 [95% CI US$-50-1316) respectively, compared to the group of patients with beta-lactam sensitive UTIs. The differences were mainly found in the use of broad-spectrum antibiotics such as meropenem, colistin and fosfomycin. Conclusion: The results of the srudy show a substantial increase in the direct medical costs of patients with UTIs caused by Beta-lactam-resistant gram-negative bacilli (cephalosporins and carbapenems). This situation is of particular concern in endemic countries such as Colombia, where the high frequencies of UTIs and resistance to Beta-lactam antibiotics can generate a greater economic impact on the health sector. © 2019 Instituto Nacional de Salud.Introducción. Las infecciones de tracto urinario (ITU) tienen una alta frecuencia en el ámbito hospitalario y debido a la emergencia de la resistencia antimicrobiana, los procesos de atención han aumentado su complejidad y demanda de recursos sanitarios. Objetivo. Describir y comparar el exceso de los costos directos médicos de las ITU por K. pneumoniae, E. cloacae y P. aeruginosa resistentes a betalactámicos. Materiales y métodos. Se realizó un estudio de cohorte en una institución de tercer nivel en Medellín-Colombia, desde octubre/2014 - septiembre/2015. Se incluyeron los pacientes con ITU por bacterias sensibles-betalactámicos, resistentes-cefalosporinas de 3ra y 4ta generación y resistentes-carbapenémicos. Los costos se analizaron desde la perspectiva del sistema de salud. La información clínico-epidemiológica se obtuvo de las historias clínicas y los costos se calcularon utilizando manuales tarifarios estándar. El exceso de costos fue estimado con análisis multivariados. Resultados. Se incluyeron 141 pacientes, 39% sensibles-betalactámicos, 38,3% resistentes-cefalosporinas y 22,7% resistentes-carbapenémicos. El exceso de costos totales ajustado de los pacientes con ITU por bacterias resistentes-cefalosporinas y carbapenémicos fue de USD$193 (IC95%, -347-734) y USD$633 (IC95%, -50-1.316) respectivamente, con respecto al grupo de pacientes con ITU sensibles-betalactámicos. Las diferencias se presentaron principalmente en el uso de antibióticos de amplio espectro como meropenem, colistina y fosfomicina. Conclusión. Los resultados evidencian un incremento sustancial de los costos directos médicos de los pacientes con ITU por bacterias resistentes a cefalosporinas y resistentes a carbapenémicos. Esta situación reviste especial preocupación en países endémicos como Colombia, donde las altas frecuencias de ITU y resistencia a betalactámicos pueden generar un mayor impacto económico al sector salud. © 2019 Instituto Nacional de Salud.